2017
DOI: 10.1021/acs.jmedchem.7b00723
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Modification within the “RPRL” Region of Apelin Peptides: Impact on Cardiovascular Activity and Stability to Neprilysin and Plasma Degradation

Abstract: Apelin is an important mammalian peptide hormone with a range of physiological roles, especially in the cardiovascular system. The apelinergic system is a promising target for treatment of disease, but this remains to be realized due to rapid proteolysis of apelin-derived peptides by proteases, including neprilysin (NEP). The synthetic analogues modified within the NEP degradation site ("RPRL" motif) showed improved in vitro proteolytic stability while maintaining receptor-binding affinities, with three candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…Apelin-17 treatment blocks progression of transplant vasculopathy. To determine whether an apelin receptor agonist treatment could modify graft coronary arterial injury, we treated recipient mice daily with the synthetic apelin receptor agonist apelin-17 peptide, which is resistant to degradation by endogenous plasma proteinases (30). Treatment was begun at 2 weeks after transplantation to model the clinical scenario of treatment of early, established injury.…”
Section: Resultsmentioning
confidence: 99%
“…Apelin-17 treatment blocks progression of transplant vasculopathy. To determine whether an apelin receptor agonist treatment could modify graft coronary arterial injury, we treated recipient mice daily with the synthetic apelin receptor agonist apelin-17 peptide, which is resistant to degradation by endogenous plasma proteinases (30). Treatment was begun at 2 weeks after transplantation to model the clinical scenario of treatment of early, established injury.…”
Section: Resultsmentioning
confidence: 99%
“…In the same group, McKinnie et al recently reported previously unidentified proteolytic cleavage sites between the Arg4‐Leu5 and Leu5‐Ser6 residues of apelin‐13, −17, and −36 by the metalloprotease neprilysin (NEP) . Subsequently, they introduced N ‐Methyl‐, α‐Methyl‐, aza ‐Arg, and ‐Leu residues to replace Arg4 and Leu5 in apelin‐13 (in combination with the above Pro12Aib and Phe13(4‐Br)Phe substitutions aimed to reduce proteolysis by NEP; Table ) . The resulting compounds bearing several modifications displayed high affinity (0.10‐1.0 nM), showing that these replacements did not harm receptor interaction.…”
Section: Structure–activity Relationship Of Apelin‐13mentioning
confidence: 99%
“…To reduce proteolysis mediated by NEP, McKinnie et al reported a series of analogues where Arg8 and Leu9 of a C ‐terminal derivative of apelin‐17 were substituted by unnatural residues (Table ) . Compared to the parent peptide 34 ( K i 0.19 nM), compounds 35–40 exhibited similar binding affinities ( K i 0.13 nM – 0.45 nM).…”
Section: Structure–activity Relationship Of Apelin‐17 and Apelin‐36mentioning
confidence: 99%
See 1 more Smart Citation
“…Peptaibiotics are constituents of a family of naturally occurring, linear peptides , 4‐ to 21‐amino acid residue long, with membrane and antibiotic activities, characterized by a very high percentage of the effective helix‐supporting, C α ‐tetrasubstituted Aib (α‐aminoisobutyric acid) residue . Their well‐known, relevant peculiarity for drug development (peptide bond stability in the presence of plasma enzymes) is strictly related to the multiple presence of this sterically highly hindered, quaternary amino acid in the primary structure. Further stability to peptidase attack is provided by their acylated N‐terminus and amidated C‐terminus.…”
Section: Introductionmentioning
confidence: 99%